Comprehensive methodology for estimating information safety at enterprises of electroenergy system under the conditions of digital coherence - Prokhorova, Viktoriia; Budanov, Oleksandr; Budanov, Pavlo; Slastianykova, Krystyna (Eastern-European Journal of Enterprise Technologies, 2025)
The object of this study is the process of assessing the information security of enterprises within an electric power system at the economy’s micro-level under the conditions of digital coherence. The work solves the task to devise a comprehensive and adaptive approach to assessing information security, taking into account modern challenges associated with the integration of digital systems. The main feature is that the methodology enables to analyze the relationships between infrastructure components, taking into account digital coherence, which makes it possible to improve the accuracy of risk assessment and the effectiveness of information security management. The devised methodology is based on eight interconnected stages, which include the integration of indicators, assessment of the interaction of system components, and monitoring changes in information security indicators in real time. This allows enterprises to respond to threats in a timely manner, minimizing risks. A computational algorithm has been developed that monitors the dynamics of changes in information security indicators, which contributes to making timely management decisions. The practical application of the methodology has been justified by scenarios of its integration into the work of energy industry enterprises. Testing at the power unit of the Zaporizhzhia Nuclear Power Plant confirmed its effectiveness, providing an economic effect of about USD 90 thousand. The methodology could be applied at different levels of the economy and adapted to the needs of specific enterprises, including integration into existing monitoring and management systems. The results demonstrate the uniqueness of the proposed approach due to its complexity, adaptability, and practical significance, which makes the methodology an effective tool for assessing information security in the context of digital coherence